A Novel 3D PILA-Type UHF RFID Tag Antenna Mountable on Metallic Objects for IoT Indoor Localization - Mondher Dhaouadi; Fethi Choubani (International Journal of Antennas and Propagation, 2021)
In this paper, a novel 3D planar inverted-L antenna (PILA) Ultrahigh Frequency (UHF) Radio Frequency Identification (RFID) tag mountable on metallic surfaces is proposed for the Internet of Things (IoT) indoor localization applications. The proposed tag antenna (45 mm × 82 mm × 4 mm or 0.137λ × 0.25λ × 0.012λ) is designed for mounting on metallic objects. The 3D PILA antenna is fabricated using a copper sheet of thickness 1 mm and air as the dielectric substrate in order to minimize costs for materials and realization. In the design, T-slot has been inserted in the radiating element for tuning of the tag’s resonance for achieving good matching with the chip. Also, a simple equivalent circuit model has been obtained to analyze the impedance of the 3D PILA. Based on the optimized design, the fabricated prototype has been measured in the anechoic chamber. The resonant frequency of the proposed tag is stable, and it is not affected much by the metallic object. The measurement results of the antenna prototype demonstrated a reasonable agreement with the simulation results, and a read range of 3.6 m was measured inside an anechoic chamber. Most importantly, in the building hallway, the proposed tag is able to achieve a maximum read distance of 18 m with a transmitted power of 31.5 dBm at 867 MHz when placed on metal. With the 3D PILA antenna structure, the proposed antimetal tag is a suitable solution that can be integrated into an indoor localization scenario.